2022
DOI: 10.2355/isijinternational.isijint-2021-577
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Composition and Structure of Triclinic SFCA-I

Abstract: The synthesis and characterisation of SFCA-I compounds has been performed. SFCA-I is one of the key bonding phases in iron ore sinter, influencing physical properties such as strength, reducibility, and strength degradation during reduction. The results reported herein extend the understanding of the solid solution limits of the SFCA-I phase, with the synthesis of single-phase SFCA-I materials containing 2.71, 3.23 and 3.73 mass% Al 2 O 3 . These materials contain less Al 2 O 3 than any previously reported SFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…25) Oxygen partial pressures during the sintering process vary between reducing as the coke burns and the flame front passes through the sinter bed, to oxidising during cooling. 26) SFCA-I has been shown to accommodate more Fe 2+ in its crystal structure than SFCA 27) and so the use of the pO 2 = 510 -3 atm throughout the entire heating and cooling regimes in these experiments is likely to have aided the formation of SFCA-I during cooling. However, we also note that in their study Kahlenberg et al observed the formation of SFCA-I in their product material after partial melting of their synthetic pellet when synthesis was conducted in air at 1573 K. 5) Zoll et al also noted the formation of SFCA-I in product material obtained after the onset melting for a pellet heated at 1723 K in air.…”
Section: Figures 1a To Cmentioning
confidence: 98%
“…25) Oxygen partial pressures during the sintering process vary between reducing as the coke burns and the flame front passes through the sinter bed, to oxidising during cooling. 26) SFCA-I has been shown to accommodate more Fe 2+ in its crystal structure than SFCA 27) and so the use of the pO 2 = 510 -3 atm throughout the entire heating and cooling regimes in these experiments is likely to have aided the formation of SFCA-I during cooling. However, we also note that in their study Kahlenberg et al observed the formation of SFCA-I in their product material after partial melting of their synthetic pellet when synthesis was conducted in air at 1573 K. 5) Zoll et al also noted the formation of SFCA-I in product material obtained after the onset melting for a pellet heated at 1723 K in air.…”
Section: Figures 1a To Cmentioning
confidence: 98%
“…In industrially produced iron ore sinter, the composition of SFCA phases varies widely [15]. Although the SFCA phase has been defined as a distinct and unique phase present in iron ore sinter, many researchers have noted that there are many other SFCA-like phases [16][17][18][19] with different morphologies and chemical compositions. SFCA and SFCA-I, SFCA-II, and SFCA-III phases containing Fe 2 O 3 , CaO, SiO 2 , and Al 2 O 3 , and insignificantly MgO and TiO 2 , are known as multicomponent calcium ferrites in agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientific research on the mineralogical composition of laboratory agglomerates-the formation of two calcium silicate phases CaO-SiO 2 , and more complicated phases of SFCA at different modes of heating and cooling-has been carried out worldwide. In the works of Australian scientists [14][15][16][21][22][23] a critical review of the research on silicoferrites of calcium and aluminum (SFCA), the main bound phases found in agglomerates, has been conducted. In particular, the papers focus on the description of the different phases of SFCA-I and the study of their phase and chemical composition, crystalline structures, and formation conditions.…”
Section: Introductionmentioning
confidence: 99%